Selection of damping coefficient of simplified mount module to control transmissibility of environmental response under nobase mass-block - Soo Lee, Gee; Yeon Lee, Moo; Hyun Kim, Ki; Jung Kim, Chan (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper focused on the simplified design of passive mount modulein electric power plants using only spring and damper elements.Methods/Statistical analysis: The selection of elements in a proposed simplified passive mount module was proceeded under the requirement, which is to show the response level same or less as compare to the case of current mount module. The response at the upper location of mount affect to negative effect on the responsible electric power plants so the design criterion should be satisfied with the newly proposed simple mount module.Findings: The frequency response function between the force and response acceleration at upper position of mount module was calculated from the theoretical mount module and the transmissibility function, between two response accelerations at two different passive mount modules, was evaluated for interesting harmonic frequencies (from 1X to 4X). The primary interesting frequency(X)was determined at 30(Hz) since the operation condition of the combustion engine in electric power plant is scheduled to be operated at constant 1,800(rev/min). Several simulation cases can be obtained for different combination of selected dampingcoefficients at the proposed mount module. The magnitude of transmissibility function should be less than one all interesting frequencies and the reasonable condition of the simple mount module can be derived from the simulation result.Then, the validation of the designed simplified mount module was conducted by preparing two kinds of mount module and the acceleration responses were measured at 1,800(rev/min) operation under 100% electric load. The spectral response at interesting frequencies confirms the superiority of the newly proposed mount module.Improvements/Applications: The simplified structure of mount module can be possible to save installation cost and time simultaneously and it is easy to conduct the maintenance of mount module.Â Â